Output DIII Jurusan Pariwisata Berbasis Enterpreneurship - Kadir, Rosma (Jurnal Pelangi Ilmu, 2012)
The research aims to elaborate the concept of human resources development based on the output of graduates and enterpreneurship Outlines enterpreneurship in tourism sphere that can be made into the entrepreneurial student majoring in tourism. The methods used in this research is descriptive qualitative research methods, the researchers describe human resources development-based entrepreneurship of graduate output. Also in this research will be outlined in a comperehensif about the realm of the corporate world in the field of tourism which should be learned by students majoring in tourism. The results of this research show that the Interconnection between entrepreneurship, tourism, and students have a holistic relationship. Where these three components must be able to synergize with each other. Students as main subject must first have an earnest desire and able to work hard in order to achieve the aspired goals. majoring in tourism can be more accommodating in view the symptoms change civilization always demanded progresivitas in innovation and creativity, in this case the necessary goodwill in making policies, including integrating entrepreneurship into the curriculum.